Characterization of novel Staphylococcus aureus lytic phage and defining their combinatorial virulence using the OmniLog® system. Issue 3 (2nd July 2016) - Estrella, Luis A.; Quinones, Javier; Henry, Matthew; Hannah, Ryan M.; Pope, Robert K.; Hamilton, Theron; Teneza-mora, Nimfa; Hall, Eric; Biswajit, Biswas
ABSTRACT: Skin and soft tissue infections (SSTI) caused by methicillin resistant Staphylococcus aureus (MRSA) are difficult to treat. Bacteriophage (phage) represent a potential alternate treatment for antibiotic resistant bacterial infections. In this study, 7 novel phage with broad lytic activity for S. aureus were isolated and identified. Screening of a diverse collection of 170 clinical isolates by efficiency of plating (EOP) assays shows that the novel phage are virulent and effectively prevent growth of 70–91% of MRSA and methicillin sensitive S. aureus (MSSA) isolates. Phage K, which was previously identified as having lytic activity on S. aureus was tested on the S. aureus collection and shown to prevent growth of 82% of the isolates. These novel phage group were examined by electron microscopy, the results of which indicate that the phage belong to the Myoviridae family of viruses. The novel phage group requires β-N-acetyl glucosamine (GlcNac) moieties on cell wall teichoic acids for infection. The phage were distinct from, but closely related to, phage K as characterized by restriction endonuclease analysis. Furthermore, growth rate analysis via OmniLog® microplate assay indicates that a combination of phage K, with phage SA0420ᶲ1, SA0456ᶲ1 or SA0482ᶲ1 have a synergistic phage-mediated lytic effect on MRSA and suppress formation of phage resistance. These results indicate that a broad spectrum lytic phage mixture can suppress the emergence of resistant bacterial populations and hence have great potential for combating S. aureus wound infections.